The Blackwell companion to religion in America - Goff, Philip (Blackwell companions to religion, 2010)
Interpreting American religion. Surveying Religion in America / Philip Goff -- Religion in American society and culture. The American Revolution / Thomas S. Kidd -- Borderlands / Kristy Nabhan-Warren -- Church and state / Derek Davis -- Civil religion / Ira Chernus -- Class and labor / Richard J. Callahan, Jr. -- Denominations / Russell E. Richey -- Economics / James Hudnut-Beumler -- Family / Rebecca L. Davis -- Film / Judith Weisenfeld -- Gender / Sarah E. Johnson -- Health / Christopher G. White -- Sensory cultures : material and visual religion reconsidered / Sally M. Promey, Shira Brisman -- Media / Robert S. Fortner -- Millennialism / Stephen J. Stein -- Missions / Wilbert R. Shenk -- Piety, practice, and ritual / Kathryn Lofton -- Popular culture / John Schmalzbauer -- Race and ethnicity / Roberto R. Trevįo -- Regions / Philip L. Barlow -- Revivals / Michael McClymond -- Science / William Durbin -- Social reform / Zoe Trodd -- Theology and belief / Robert E. Brown -- Women / Susanna Morrill -- Traditions and movements. American Indians / Tracy Neal Leavelle -- Anabaptists / David L. Weaver-Zercher -- Baptists / Paul Harvey -- The Black Church / Sylvester Johnson -- Buddhism / Charles S. Prebish -- Catholicism to 1945 / Michael Pasquier -- Catholicism since 1945 / Philip Gleason -- Church of Jesus Christ of Latter-Day Saints / David J. Whittaker -- Eastern Orthodox Christianity / Amy A. Slagle -- Evangelicalism / Darren Dochuk -- Hinduism / Khyati Y. Joshi -- Holiness and Pentecostalism / Jonathan R. Baer -- Islam / Edward E. Curtis IV -- Judaism / Yaakov Ariel -- Lutherans / Susan Wilds McArver -- New and homegrown religions / Sean McCloud -- Protestant Liberalism / Mark Hulsether -- Reformed tradition / D.G. Hart -- Wesleyan tradition / Christopher H. Evans